Identification of the PfK13 mutations R561H and P441L in the Democratic Republic of Congo - Gauthier Mesia Kahunu; Sarah Wellmann Thomsen; Louise Wellmann Thomsen; Hypolite Muhindo Mavoko; Patrick Mitashi Mulopo; Emma Filtenborg Hocke; Papy Mandoko Nkoli; Vito Baraka; Daniel T.R. Minja; Andria Mousa; Cally Roper; Destin Mbongi Moke; et al. (International Journal of Infectious Diseases, 2024)
Objectives: Partial artemisinin resistance, mediated by Plasmodium falciparum K13 (PfK13) mutations, has been confirmed in certain areas of East Africa that are historically associated with high-level antimalarial resistance. The Democratic Republic of Congo (DRC) borders these areas in the East. This study aimed to determine the prevalence of resistance markers in six National Malaria Control Program surveillance sites; Boende, Kabondo, Kapolowe, Kimpese, Mikalayi, and Rutshuru. Methods: The single nucleotide polymorphisms (SNPs) in P. falciparum genes PfK13, Pfdhfr, Pfdhps, Pfmdr1, and Pfcrt were assessed using targeted next-generation sequencing of isolates collected at enrollment in therapeutic efficacy studies. Results: PfK13 SNPs were detected in two samples: in Kabondo (R561H) and in Rutshuru (P441L), both areas near Uganda and Rwanda. The Pfdhps ISGEGA haplotype, associated with reduced sulfadoxine-pyrimethamine chemoprevention efficacy, ranged from 0.8% in Mikalayi (central DRC) to 42.2% in Rutshuru (East DRC). Conclusions: R561H and P441L observed in eastern DRC are a concern, as they are associated with delayed artemisinin-based combination therapies-clearance and candidate marker of resistance, respectively. This is consistent with previous observations of shared drug resistance profiles in parasites of that region with bordering areas of Rwanda and Uganda. The likely circulation of parasites has important implications for the ongoing surveillance of partial artemisinin-resistant P. falciparum and for future efforts to mitigate its dispersal.